Des interventions musicales en groupe pour favoriser le développement social d’enfants ayant un trouble du spectre de l’autisme : une revue de la littérature - Bédard-Bruyère, Flavie; Bolduc, Jonathan; Després, Jean-Philippe (Canadian Journal of Education/Revue canadienne de l'éducation, 2022)
Autism spectrum disorder is a neurodevelopmental disorder that particularly affects social and language skills. Many intervention methods have been developed to help individuals with autism cope with these challenges. Some make use of the arts, such as music therapy. This article reviews the literature on music group interventions to examine how they foster social development in children with autism. Six databases were searched and seven articles that met the inclusion criteria were reviewed. The research findings are discussed and future directions are proposed.